2016
DOI: 10.1177/1758834016657071
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and targets in triple-negative breast cancer: recent results and clinical implications

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous disease in which tumors are defined by lack of expression of the estrogen receptor (ER), the progesterone receptor (PR), and the human epidermal growth factor receptor 2 (HER2) receptor. No targeted therapies are available for the treatment of TNBC, and chemotherapy remains the standard of care. Gene expression profiling has identified six distinct molecular subtypes of TNBC. The identification of novel targets, coupled with the development of therapies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…[10][11][12][13][14] According to clinical studies, response rates to anti-PD-1/PD-L1 therapy range between 5 to 23% within advanced TN breast cancer patients. 15 Higher response rates are linked with PD-L1 positivity. 15 However, not all PD-L1-positive (PD-L1+) tumors respond to anti-PD-1/PD-L1 therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] According to clinical studies, response rates to anti-PD-1/PD-L1 therapy range between 5 to 23% within advanced TN breast cancer patients. 15 Higher response rates are linked with PD-L1 positivity. 15 However, not all PD-L1-positive (PD-L1+) tumors respond to anti-PD-1/PD-L1 therapy.…”
Section: Introductionmentioning
confidence: 99%
“…15 Higher response rates are linked with PD-L1 positivity. 15 However, not all PD-L1-positive (PD-L1+) tumors respond to anti-PD-1/PD-L1 therapy.…”
Section: Introductionmentioning
confidence: 99%
“…8E). The expression of IL-1α was very low in MCF-7 6 cells when compared to SUM159 and thus these experiments were not performed in the former cell line. These results indicated that IL-1α is a direct transcriptional target of FoxQ1 at least in the SUM159 cell line.…”
Section: Il-1α Il-8 and Vegf Are Novel Downstream Transcriptional Tmentioning
confidence: 99%
“…Majority of the invasive mammary ductal carcinomas are broadly grouped into four subtypes, including luminal A type [estrogen receptor positive (ER+ 3 ), progesterone receptor positive (PR+), and human epidermal growth factor receptor 2 positive (HER2+)], luminal B type (ER+/PR+/HER2-), HER2enriched, and basal-like (2,3). Nearly 75% of basal-like breast tumors are triplenegative due to lack of ER, PR, and HER2 expression (6). Further characterization of the disease subtype-independent oncogenic dependencies in breast cancer is necessary to identify novel druggable targets to broaden therapeutic options for different subtypes of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Well studied therapeutic targets for TNBC include those proteins in proliferative and survival-dependent pathways, such as epidermal growth factor receptor (EGFR) [16,17], vascular endothelial growth factor receptor (VEGFR) [18], JAK2/STAT3 [19] and PI3K [20,21,22,23], and those control the cell cycle and the DNA damage responses such as Poly-ADP Ribose Polymerase (PARPs) [24,25]. However, the initial results of candidate compounds targeting these proteins from clinical trials [3,26,27,28,29,30] remain modest, highlighting the importance of systematic target discovering, assessing and prioritizing for biological validation and therapeutic exploitation.…”
Section: Introductionmentioning
confidence: 99%